STRATEGI PENGEMBANGAN LEMBAGA PERKREDITAN DESA DI BALI - Wiagustini, Ni Luh Putu; Panji Sedana, Ida Bagus; Yeni Astiti, Ni Putu; Pryanka Maharani, Ida Ayu Dinda (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023, 2023)
The Village Credit Institution is a Microfinance Institution based on local wisdom in Bali, which has the aim of improving the Village economy, currently facing competition from similar financial institutions operating in Bali. Based on this, the aim of this research is to analyze the internal and external environment as a basis for formulating strategies for empowering Village . Credit . Institutions . in Bali. The sample for this research was 100 Village Credit Institutions in Bali which were taken using stratified proportional random sampling based on districts/cities. Data was analyzed using SWOT Analysis, which is outlined . in the External . Factor . Analysis Summary (EFAS) and Internal . Factor . Analysis Summary (IFAS) matrices. This research found that the Village Credit Institution empowerment strategy in Bali in the future can be carried out with an intensive strategy through market penetration strategies and new product development. The penetration strategy includes increasing credit customers and third party funds more intensively and the new product development strategy includes funding micro and small businesses with a profit sharing system, funding household equipment and term savings.